Impact of Covid-19 on the South African economy: An initial analysis - Arndt, Channing; Davies, Rob; Gabriel, Sherwin; Harris, Laurence; Makrelov, Konstantin; Modise, Boipuso; Robinson, Sherman; Simbanegavi, Witness; van Seventer, Dirk; Anderson, Lillian (United Nations University, 2020)
This paper reports ‘first pass’ estimates of the costs of the lock-down implemented by the South African government beginning on 27 March 2020. It also presents a series of recovery scenarios. Four channels by which a lockdown and other efforts are expected to influence economic activity are distinguished. In total, these lockdown measures have profound economic implications. The implications of the pandemic in the rest of the world, and hence on demand for South Africa’s export, are not as large as the effects of the domestic lockdown but are still very large by any normal measure. In terms of recovery, the ‘Quick’ recovery scenario results in a GDP decline of about 5 per cent by the end of 2020—an economic outcome that would have been considered catastrophically bad a little more than one month ago. Persistent effects of the Covid-19 would bring even worse outcomes for GDP in line with the ‘Slow’ and ‘Long’ recovery scenarios.